Sinus bone graft and simultaneous vertical ridge augmentation: case series study - Dong-Woo Kang; Pil-Young Yun; Yong-Hoon Choi; Young-Kyun Kim (SpringerOpen, 2019)
Abstract Background This study aims to examine the outcome of simultaneous maxillary sinus lifting, bone grafting, and vertical ridge augmentation through retrospective studies. Methods From 2005 to 2010, patients with exhibited severe alveolar bone loss received simultaneous sinus lifting, bone grafting, and vertical ridge augmentations were selected. Fifteen patients who visited in Seoul National University Bundang Hospital were analyzed according to clinical records and radiography. Postoperative complications; success and survival rate of implants; complications of prosthesis; implant stability quotient (ISQ); vertical resorption of grafted bone after 1, 2, and 3 years after surgery; and final observation and marginal bone loss were evaluated. Results The average age of the patients was 54.2 years. Among the 33 implants, six failed to survive and succeed, resulting in an 81.8% survival rate and an 81.8% success rate. Postoperative complications were characterized by eight cases of ecchymosis, four cases of exposure of the titanium mesh or membrane, three cases of peri-implantitis, three cases of hematoma, two cases of sinusitis, two cases of fixture fracture, one case of bleeding, one case of numbness, one case of trismus, and one case of fixture loss. Prosthetic complications involved two instances of screw loosening, one case of abutment fracture, and one case of food impaction. Resorption of grafted bone material was 0.23 mm after 1 year, 0.47 mm after 2 years, 0.41 mm after 3 years, and 0.37 mm at the final observation. Loss of marginal bone was 0.12 mm after 1 year, and 0.20 mm at final observation. Conclusions When sinus lifting, bone grafting, and vertical ridge augmentation were performed simultaneously, postoperative complications increased, and survival rates were lower. For positive long-term prognosis, it is recommended that a sufficient recovery period be needed before implant placement to ensure good bone formation, and implant placement be delayed.